2013
DOI: 10.4103/1319-3767.111955
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory efficiency of Ankaferd blood stopper in experimental distal colitis model

Abstract: Background/Aim:Ankaferd blood stopper (ABS) is a herbal extract that enhances mucosal healing. In this study, we aimed to investigate the efficiency of ABS in the treatment of experimental distal colitis.Materials and Methods:Twenty one male albino rats were divided into three groups: Sham control (Group 1), colitis induced by acetic acid and treated with saline (Group 2), colitis induced by acetic acid and treated with ABS (Group 3). At end of the 7th day of induction, all the rats were lightly anesthetized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
(26 reference statements)
1
20
0
Order By: Relevance
“…41 Kocak et al suggested that ABS had an antioxidant action in the intestine in an experimental distal colitis model which could be attributed to herbal mixtures including G glabra and T. Vulgaris. 42 Consistent with these results in our study, ABS treatment significantly increased SOD activity in the warfarin group at the end of the eighth day when compared to the no hemostatic agent applied group. The SOD is an enzyme that repairs cells and reduces the damage done to them by superoxide, the most common free radical in the body.…”
Section: Discussionsupporting
confidence: 91%
“…41 Kocak et al suggested that ABS had an antioxidant action in the intestine in an experimental distal colitis model which could be attributed to herbal mixtures including G glabra and T. Vulgaris. 42 Consistent with these results in our study, ABS treatment significantly increased SOD activity in the warfarin group at the end of the eighth day when compared to the no hemostatic agent applied group. The SOD is an enzyme that repairs cells and reduces the damage done to them by superoxide, the most common free radical in the body.…”
Section: Discussionsupporting
confidence: 91%
“…Besides its homeostatic activity, Kocak et al 29 reported that Ankaferd might also have anti-inflammatory effects 7. Tests have demonstrated its safety, efficacy, sterility and non-toxicity for external usage 8,30…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Besides from these hemostatic properties, the anti-inflammatory effect of ABS are reported to be based on the effect of proinflammatory cytokines including tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and its antioxidant potential. [8][9][10] Difficult to cure in nature, inflammation of the cervix can be treated with topical application of ABS based on its anti-inflammatory effect, which was proved in several studies. 10,11 Unfortunately, to our knowledge, no study in the literature evaluates the beneficial effect of ABS explicitly on inflammatory response during cervicitis.…”
Section: Groupsmentioning
confidence: 99%
“…[8][9][10] Difficult to cure in nature, inflammation of the cervix can be treated with topical application of ABS based on its anti-inflammatory effect, which was proved in several studies. 10,11 Unfortunately, to our knowledge, no study in the literature evaluates the beneficial effect of ABS explicitly on inflammatory response during cervicitis. Therefore, in this study, we attempted to define and characterize the possible role of ABS in the elimination of a chronic inflammatory process in a rat model of cervicitis.…”
Section: Groupsmentioning
confidence: 99%